THE REORGANIZATION OF PLANT GENOMES DURING ALLOPOLYPLOIDISATION - A. B. Shcherban (Вавиловский журнал генетики и селекции)
Molecular mechanisms governing plant genome reorganization in the course of allopolyploidization are reviewed. The special role of early genetic changes, which were studied by using a unique model of synthetic allopolyploids, is emphasized. The data on various genomic changes at early stages of allopolyploidization, including activation of mobile elements, chromosomal rearrangements, epigenetic and transcriptomic changes, etc., are summarized. We note that these changes provide evolutionary success of allopolyploids and their prevalence among higher plants due to formation of stable organization of the allopolyploid genome.